A Comparison of New Pharmacological Agents for the Treatment of Obesity. (May 2016) - Nuffer, Wesley; Trujillo, Jennifer M.; Megyeri, Jade
Objective: To review and compare the phase 3 clinical trial evidence on the 4 new pharmacological agents approved for the management of overweight and obesity.Data Sources: Searches were performed (from 1966 through January 2016) in PubMed/MEDLINE, Scientific Citation Index, and product package inserts to identify key phase 3 clinical trials that were used in the approval of each agent.Study Selection and Data Extraction: Phase 3 clinical trials that listed end points of ≥5% and ≥10% weight loss benchmarks from baseline as well as total percentage of weight loss by participants were selected for the review.Data Synthesis: No head-to-head trials have been identified between these agents at this point, which limits comparisons across agents. Phentermine/topiramate ER appeared to have the best overall average weight loss from baseline as well as highest percentages of patients achieving both ≥5% and ≥10% weight loss benchmarks, followed second by naltrexone/bupropion, and then liraglutide, with lorcaserin showing the lowest rates. Phentermine/topiramate ER completion rates were highest for both treatment and placebo groups, followed by liraglutide, with lorcaserin and naltrexone/bupropion showing similar completion rates, below that of the other 2 agents. Common side effects reported differed between agents, although the most common adverse events reported were gastrointestinal in nature, with liraglutide demonstrating the highest reported rates and lorcaserin demonstrating the lowest.Conclusion: These 4 new pharmacological agents represent new options for the clinician to utilize when trying to manage the problem of obesity. No clear first-line agent has emerged, so treatment decisions should be based on patient-specific factors.